Controlling Mechanism of Rock Burst by CO2 Fracturing Blasting Based on Rock Burst System - Tianwei Lan; Chaojun Fan; Jun Han; Hongwei Zhang; Jiawei Sun (Shock and Vibration)
Rock burst induced by mining is one of the most serious dynamic disasters in the process of coal mining. The mechanism of a rock burst is similar to that of a natural earthquake. It is difficult to accurately predict the “time, space, and strength” of rock burst, but the possibility of rock burst can be predicted based on the results of microseismic monitoring. In this paper, the rock burst system under the tectonic stress field is established based on the practice of coal mining and the result of mine ground crustal stress measurement. According to the magnitude of microseismic monitoring, the amount of the energy and spatial position of the rock burst are determined. Based on the theory of explosion mechanics, aiming at the prevention and control of rock burst in the coal mine, the technique of liquid CO2 fracturing blasting is put forward. By the experiment of blasting mechanics, the blasting parameters are determined, and the controlling mechanism of rock burst of liquid CO2 fracturing blasting is revealed. The application of liquid CO2 fissure blasting technology in the prevention and control of rock burst in Jixian Coal Mine shows that CO2 fracturing blasting reduces the stress concentration of the rock burst system and transfers energy to the deeper part, and there is no open fire in the blasting. It is a new, safe, and efficient method to prevent and control rock burst, which can be applied widely.